AKTIVITAS EKSTRAK KULIT BATANG LANGSAT (Lansium parasiticum (Osbeck) Sahni & Bennet) TERHADAP KELARUTAN KALSIUM BATU GINJAL SECARA in vitro - Nur Ramadhani; Yuliet Yuliet; Khildah Khaerati (Biology Department, Mathematics and natural science, Tadulako University, 2018)
The kidney stone is a stone which is found in the kidney or other parts of urinary tract. The most frequently type of stone encountered are composed of calcium crystals. As much as 60% content of kidney stones consist of calcium oxalate, phosphate, carbonate, uric acid, magnesium, and ammonium. Langsat (Lansium parasiticum (Osbeck) Sahni & Bennet) is a plant that may dissolve kidney stones and smooth urination, particularly its bark. This study aims to determine the activity as well as the greatest concentration of Langsat bark ethanol extract in dissolving dissolves calcium of kidney stones conducted in vitro. The ethanol extract was obtained by maceration method using 96% ethanol followed by phytochemical screening test and thin layer chromatograpy (TLC) profiling of the extract. Chromatogram result shows that the extract contains flavonoids. The research methodology conducted was the kidney stone powder dissolution in the ethanol extract of Langsat bark after being destructed with concentrations of respectively 0.5%, 1% and 1.5% then incubated in 37ºC temperature for 3 hours. The solubility of calcium was assayedby measuring the calcium (Ca) levelsat the beginning and at after being incubated with the kidney stone.The positive control used was Calcusol® and the negative onewas aquadest. The dissolved calcium levels were measured by using Atomic Absorption Spectrophotometer at λ = 422.7 nm. The research results show that Langsat Bark ethanol extract has the activity in dissolving the calcium of kidney stones in vitro of which concentration with greatestactivity of calcium dissolution is 1.5% w/v. Keywords: Kidney Stone, Langsat, Lansium parasiticum, Calcium.